PRINSIP-PRINSIP PAK ANAK: SEBUAH KAJIAN EKSEGESIS ALKITAB DARI ULANGAN 6: 4-9 - Evinta Hotmarlina; Maria A. S. Sondjaja (Phronesis: Jurnal Teologi dan Misi, 2022)
This article seeks to research principles of Christian Religious Education through exegeting Deuteronomy 6:4-9. This research uses the qualitative-descriptive method. Principles of Christian Religious Education constructed based on Deuteronomy 6:4-9 could generate balanced emphases between academic ability and spiritual formation; both are vital to equip the younger generations to face global challenges. Thus, the purpose of Christian Religious Education for children is to build a younger generation that could contribute to the broader society based on solid Christian principles. Deuteronomy 6:4-9 is guidance for parents to practice Christian Religious Education in the family. Family should be the first place for children to confess that there is only one true God, love God, do His instructions, discuss His law, reflect upon it, and bear witness to the one true God.